1994
DOI: 10.1007/bf00188300
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of adrenalectomy via operative laparoscopy

Abstract: Adrenalectomy is usually performed through a transabdominal or a posterior approach. These approaches are associated with a painful syndrome postoperatively and long hospital stay. We report a series of five successful laparoscopic adrenalectomies, performed on: a 35-year-old male with a 5-cm right nonfunctioning tumor; a 32-year-old female with a 1.8-cm right aldosterone-producing adenoma; a 17-year-old female with a 4-cm right adrenocortical adenoma; and a 33-year-old female with bilateral 3.5-cm right and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Comparable circulatory responses observed using the transperitoneal and retroperitoneal techniques suggest that, in accordance with results reported by Bonjer et al [2], early adrenal vein ligation may not be mandatory. However, nonmanipulative dissection of the gland and ligation of all venous branches visualized are essential to avoid the development of intraoperative blood pressure peaks [4,6,14,19]. Because neovascularization is frequently observed with pheochromocytomas, catecholamines may enter the circulation not only via the adrenal vein, but also through a number of additional venous side branches [1].…”
Section: Discussionmentioning
confidence: 99%
“…Comparable circulatory responses observed using the transperitoneal and retroperitoneal techniques suggest that, in accordance with results reported by Bonjer et al [2], early adrenal vein ligation may not be mandatory. However, nonmanipulative dissection of the gland and ligation of all venous branches visualized are essential to avoid the development of intraoperative blood pressure peaks [4,6,14,19]. Because neovascularization is frequently observed with pheochromocytomas, catecholamines may enter the circulation not only via the adrenal vein, but also through a number of additional venous side branches [1].…”
Section: Discussionmentioning
confidence: 99%
“…The main development in this technique has been the complete lateral position of the patient described initially by Gagner [16], avoiding the disadvantages of the transperitoneal approach observed in a patient placed in a supine position. In fact, the transperitoneal approach for a patient in the decubitus position, described initially by Fernandez-Cruz et al [28] is no longer advocated. It has many drawbacks, including the need for five or six ports.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember to have instruments that are long enough for heavily built patients. The approach in this lateral position allows easy vessel control and adrenal gland dissection, whereas this is more difficult with the patient in the decubitus prone position [2,3,8]. The lateral decubitus position makes the intraabdominal organs anterior to the adrenal gland rotate due to the effect of gravity; this rotation helps their retraction [4,5] and offers good exposure even in the case of big tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Later several reports of laparoscopic adrenalectomies were published [2][3][4][5][6]9]; they showed that laparoscopic surgery, which was initially confined to abdominal pathology, is also useful for retroperitoneal procedures, such as the resection of adrenal glands. This paper reports our experience with laparoscopic adrenalectomy in 27 consecutive patients (30 adrenalectomies; three bilateral) with different adrenal pathology.…”
mentioning
confidence: 99%